Acrylic resin and preparation method and application thereof, low-friction acrylic paint and application thereof, low-friction acrylic coating and preparation method and application thereof

By introducing degradable polymerizable silicone monomers into the acrylic resin hydrolyzed under weak alkaline conditions, a low-friction acrylic coating with a gradual controllable interface hydration was prepared, which solved the problem of loss of existing lubricating coatings in a long-term service environment, and achieved high stability, wear resistance and green and environmentally friendly lubricating effects.

CN119751736AActive Publication Date: 2025-04-04LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411441142.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-04-04
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing lubricating coatings are prone to irreversible loss in long-term service environments, which limits the realization of lubricating properties of imitating natural joints and lacks green and environmentally friendly characteristics.

Method used

A low friction acrylic coating with a stepwise controlled interface hydration was prepared by polymerizing a degradable polymerizable silicone monomer, non-degradable acrylic monomer and acrylate monomer by using acrylic resin hydrolyzed under weakly alkaline conditions.

Benefits of technology

It realizes the characteristics of controllable degradation rate, good stability, good wear resistance, and self-updating of the wear interface, and also has green and environmentally friendly characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751736A_ABST
    Figure CN119751736A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating functional materials, and particularly relates to acrylic resin and a preparation method and application thereof, a low-friction acrylic coating and application thereof, and a low-friction acrylic coating and a preparation method and application thereof. The invention provides an acrylic resin hydrolyzed under a weak alkaline condition. The invention relates to a low-friction acrylic coating which comprises acrylic resin hydrolyzed under weak alkaline conditions and has a degradable property and a low-friction acrylic coating which comprises the low-friction acrylic coating with the degradable property and has the characteristic of gradually controllable hydrolysis of an interface. A low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of an interface, which is formed by the degradable low-friction acrylic coating obtained from the acrylic resin hydrolyzed under the weak alkaline condition, has the characteristics of controllable degradation rate, good wear resistance and self-renewal of a worn interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating functional materials, and specifically relates to acrylic resin and a preparation method and application thereof, low-friction acrylic paint and application thereof, and low-friction acrylic coating and a preparation method and application thereof. Background Art

[0002] Lubricating materials with low friction coefficient and good wear resistance are an effective way to solve typical wear problems in the fields of mechanical friction, biological lubrication, etc. In particular, the design of ultra-low friction systems is of great significance to the fields of energy environment, mechanical transportation, etc. Affected by the inevitable wear behavior, it is particularly important to achieve long-life wear-resistant materials with low friction characteristics. For example, Aizenberg et al. from Harvard University in the United States reported the super-slippery interface (SLIPS) of lubricating liquid-filled porous substrates. This technology locks or injects the lubricating liquid into the porous matrix through porous materials. Under long-term service conditions, the surface has a lower friction coefficient due to the dynamic replenishment of the lubricating liquid film. And the continuous sacrifice of this lubricating interface under wear conditions is instantly replenished due to the continuous seepage of the lubricating oil components, which can ensure more lasting low-friction characteristics. In addition, Chinese Patent 202011158727.4 reported a silicone oil-containing lubricating coating with a low friction coefficient, which uses low molecular weight silicone oil and polyurethane resin to construct a room temperature solid-liquid separation coating, and realizes the controllable release of silicone oil lubricating components under the stimulation of friction motion, reducing the friction coefficient while extending the wear-resistant period. Chinese Patent 201910735154.8 reported a method for preparing an ultra-low friction coefficient self-lubricating coating composed of lubricant capsules and a reinforcing phase, which also uses the continuous seepage of lubricating components during the friction process to achieve the construction of a wear-resistant lubrication system with low friction characteristics. However, the above-mentioned lubricating coating does not have the characteristics of green and environmental protection.

[0003] Furthermore, the increasingly prominent environmental problems have made the development of green and environmentally friendly low-friction systems more and more prominent. The principle of natural joint lubrication shows that the combination of highly hydrated interface and high-load-bearing substrate can ensure the characteristics of high load-bearing, low friction and long life. Among them, the highly hydrated interface has typical water lubrication characteristics and wear resistance, while the high-load-bearing substrate exhibits good load-bearing characteristics through stress dispersion. Therefore, under the premise of green environmental protection, in order to realize the preparation of bionic gradient materials with strong interface hydration and high bottom load characteristics, soft matter-based viscoelastic materials show unique advantages.

[0004] However, highly hydrated friction-reducing interfaces usually undergo irreversible wear under long-term service conditions. Therefore, the stability and wear resistance of highly hydrated interfaces based on soft materials become the main factors limiting the preparation of artificial materials that mimic the lubrication properties of natural joints. Summary of the invention

[0005] The purpose of the present invention is to provide acrylic resin and its preparation method and application, low-friction acrylic paint and its application, low-friction acrylic coating and its preparation method and application. The low-friction acrylic coating with gradually controllable interfacial hydration provided by the present invention has the characteristics of controllable degradation rate, good stability, good wear resistance and self-renewal of wear interface.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides an acrylic resin hydrolyzed under weak alkaline conditions, which is obtained by polymerizing the following raw materials in parts by weight:

[0008] 10-15 parts of degradable polymerizable silicone monomer, 30-60 parts of the sum of non-degradable acrylic acid monomer and non-degradable acrylate monomer, 1-1.5 parts of initiator, 50-75 parts of organic solvent;

[0009] The non-degradable acrylic acid ester monomer comprises a first acrylic acid ester monomer, a second acrylic acid ester monomer and β-hydroxyethyl methacrylate, wherein the first acrylic acid ester monomer comprises methyl methacrylate and / or ethyl acrylate, and the second acrylic acid ester monomer comprises butyl acrylate and / or methoxyethyl methacrylate;

[0010] The structural formula of the degradable polymerizable silicone monomer is shown in Formula I:

[0011]

[0012] In formula I, R1 is H or methyl.

[0013] Preferably, the non-degradable acrylic acid ester monomers include methyl methacrylate, butyl acrylate and β-hydroxyethyl methacrylate;

[0014] The mass ratio of methyl methacrylate, butyl acrylate, β-hydroxyethyl methacrylate and non-degradable acrylic acid monomer is (4-8):(6-10):(8-12):(12-16);

[0015] The initiator is azobisisobutyronitrile.

[0016] The present invention provides a method for preparing an acrylic resin hydrolyzed under weak alkaline conditions as described in the above technical solution, comprising the following steps:

[0017] A degradable polymerizable silicone monomer, a non-degradable acrylic acid monomer, a non-degradable acrylate monomer, an initiator and an organic solvent are mixed to obtain a mixed solution; the mixed solution is subjected to a polymerization reaction to obtain an acrylic resin hydrolyzed under the weak alkaline condition.

[0018] Preferably, the polymerization reaction temperature is 85-95° C.; the polymerization reaction comprises the following steps:

[0019] Conducting a first-stage polymerization reaction on a portion of the mixed solution to obtain a prepolymerization reaction solution, wherein the reaction time of the first-stage polymerization reaction is 25 to 40 minutes;

[0020] The remaining mixed solution is added dropwise to the prepolymerization reaction liquid to carry out a second stage polymerization reaction to obtain an acrylic resin hydrolyzed under the weak alkaline condition. The dropping speed is 0.8 to 1.2 mL / min. After the dropping is completed, the insulation reaction time of the second stage polymerization reaction is 2 to 3 hours.

[0021] The present invention provides the use of the acrylic resin hydrolyzed under weak alkaline conditions described in the above technical solution or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in the above technical solution in a low-friction acrylic coating with degradable characteristics.

[0022] The present invention provides a low-friction acrylic paint with degradable properties, comprising the following components in parts by weight:

[0023] 40-60 parts of acrylic resin hydrolyzed under weak alkaline conditions;

[0024] 10-15 parts of wear-resistant filler;

[0025] 10-15 parts of pigments and fillers;

[0026] 1-2 parts of auxiliary agent;

[0027] 15-25 parts of organic solvent;

[0028] The acrylic resin hydrolyzed under weak alkaline conditions is the acrylic resin hydrolyzed under weak alkaline conditions described in the above technical solution or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in the above technical solution.

[0029] Preferably, the wear-resistant filler comprises precipitated barium sulfate, mica powder and brown corundum; the mass ratio of the precipitated barium sulfate, mica powder and brown corundum is (1-1.8):(1-1.8):(1-2);

[0030] The pigment filler comprises organic bentonite, kaolin, red iron oxide and zinc oxide; the mass ratio of the organic bentonite, kaolin, red iron oxide and zinc oxide is (1-1.8):(1-1.8):(1-2):1;

[0031] The auxiliary agents include a wetting and dispersing agent, a leveling agent, a defoaming agent and an anti-settling agent; the mass ratio of the wetting and dispersing agent, the leveling agent, the defoaming agent and the anti-settling agent is (1-3):(1-2):(1-2):(1-2).

[0032] The present invention provides the use of the low-friction acrylic paint with degradable characteristics described in the above technical solution in a low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of the interface.

[0033] The present invention provides a low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of the interface, comprising the following raw materials in parts by weight: 10 to 20 parts of the low-friction acrylic coating with degradable characteristics described in the above technical solution and 0.1 to 0.3 parts of a crosslinking agent.

[0034] The present invention provides a method for preparing a low-friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface as described in the above technical solution, comprising the following steps:

[0035] The low-friction acrylic coating crosslinking agent with degradable characteristics described in the above technical solution is mixed with an organic solvent and then coated on the surface of the substrate to obtain an initial wet film;

[0036] The initial wet grinding is dried to obtain a low-friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface on the surface of the substrate.

[0037] The present invention provides the use of the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis as described in the above technical solution or the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis prepared by the preparation method described in the above technical solution as a lubricating material in an alkaline environment.

[0038] The invention provides an acrylic resin hydrolyzed under weak alkaline conditions, which is obtained by polymerizing the following raw materials in parts by mass: 10 to 15 parts of a degradable polymerizable silicone monomer, 30 to 60 parts of a non-degradable acrylic acid monomer and a non-degradable acrylic acid ester monomer, 1 to 1.5 parts of an initiator, and 50 to 75 parts of an organic solvent; the non-degradable acrylic acid ester monomer comprises a first acrylic acid ester monomer, a second acrylic acid ester monomer, and β-hydroxyethyl methacrylate, the first acrylic acid ester monomer comprises methyl methacrylate and / or ethyl acrylate, and the second acrylic acid ester monomer comprises butyl acrylate and / or methoxyethyl methacrylate; the degradable polymerizable silicone monomer is an acrylic acid silicone ester monomer, and its structural formula is shown in Formula I. In the present invention, the degradable polymerizable silicone monomer, the non-degradable acrylic acid and acrylic acid ester compound monomer provide an acrylic resin matrix component that is hydrolyzed under weak alkaline conditions, and the degradable silicone monomer gives the acrylic resin a degradable property, so that the coating has stable degradation performance in a weak alkaline environment (pH value is 8-9) (degradation performance, i.e., hydrolysis performance, refers to the behavior of Si-O bonds in the coating breaking under a weak alkaline environment), the degraded silicone monomer produces a hydrophilic carboxyl group, and a micron-scale porous structure appears on the surface of the degraded coating, further improving the self-lubricating performance of the coating; the β-hydroxyethyl methacrylate gives the self-lubricating acrylic resin a cross-linkable property, and when preparing the coating, in the cross-linking agent (in the embodiment, Under the action of an isocyanate cross-linking agent), a cross-linking reaction can be achieved at room temperature, which is beneficial to improving the stability and mechanical properties of the self-lubricating acrylic resin. At the same time, through the synergistic effect with the cross-linking agent, the controllable hydrolysis characteristics of the coating are guaranteed; the introduction of the acrylic acid (i.e., the non-degradable acrylic monomer) is beneficial to improving the hydrophilicity of the coating containing the self-lubricating acrylic resin, and is beneficial to building a hydrated lubricated interface; the introduction of the second acrylate monomer (preferably butyl acrylate in the embodiment) is beneficial to improving the flexibility of the self-lubricating acrylic resin and improving the toughness of the coating; the initiator (such as azobisisobutyronitrile) is beneficial to promoting the graft copolymerization of the raw materials for preparing the self-lubricating acrylic resin, and at the same time improving the bonding ability of the self-lubricating acrylic resin obtained by graft copolymerization with the coated substrate.

[0039] The present invention provides a low-friction acrylic coating with degradable characteristics, comprising the following components in parts by mass: 40 to 60 parts of acrylic resin hydrolyzed under weak alkaline conditions; 10 to 15 parts of wear-resistant fillers; 10 to 15 parts of pigments and fillers; 1 to 2 parts of additives; and 15 to 25 parts of organic solvents; the acrylic resin hydrolyzed under weak alkaline conditions is the acrylic resin hydrolyzed under weak alkaline conditions described in the above technical solution or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in the above technical solution. In the present invention, the wear-resistant filler is beneficial to improving the mechanical properties and wear resistance of the low-friction acrylic coating with the characteristics of gradually controllable hydrolysis of the interface; the additives and organic solvents are beneficial to reducing the viscosity of the low-friction acrylic coating with degradable characteristics, improving the film-forming performance, improving the uniformity and continuity of the coating film, and enhancing the adhesion of the coating film to the substrate.

[0040] The present invention provides a low-friction acrylic coating with the characteristic of gradual controllable hydrolysis of the interface ("hydrolysis" and "degradation" have the same meaning in the present invention), comprising the following raw materials by mass: 10 to 20 parts of the low-friction acrylic coating with degradable characteristics described in the above technical scheme and 0.1 to 0.3 parts of a crosslinking agent. The low-friction acrylic coating with the characteristic of gradual controllable hydrolysis provided by the present invention is formed by a crosslinking reaction between the low-friction acrylic coating with degradable characteristics described in the above technical scheme (including an acrylic resin that can be hydrolyzed under weak alkaline conditions, wear-resistant fillers, pigment fillers, and additives, etc.) and a crosslinking agent. In the present invention, the acrylic resin hydrolyzed under weak alkaline conditions ensures that the interface is gradually degraded to form a water lubrication layer, and the crosslinking agent is beneficial to improving the stability and wear resistance of the coating. At the same time, by controlling the content of the crosslinking agent in the coating, the hydrolysis rate of the coating can be controlled, giving the coating the characteristic of controllable degradation. The wear-resistant filler ensures that the coating has good wear resistance. The acrylic coating prepared by this feature is jointly determined by the acrylic silicon content and chemical crosslinking to form a degradation hydration layer at the micron scale under weak alkaline conditions. Combined with wear-resistant fillers, it has a low interface friction coefficient and stable wear resistance. This feature takes into account the characteristics of top surface friction reduction and bottom surface wear resistance. And the micron-scale hydration layer can be continuously renewed as the interface wears, and has a typical low-friction self-renewal characteristic. Finally, the low-friction acrylic coating with gradually controllable hydrolysis characteristics provided by the present invention has a certain fluid drag reduction efficiency.

[0041] The test results of the embodiment show that the low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of the interface formed by the low-friction acrylic coating with degradable characteristics obtained by hydrolyzing the acrylic resin under weak alkaline conditions provided by the present invention has a grade 1 adhesion to the epoxy substrate and a high bonding force; the degradation rate of the coating is controllable, and the degradation rate decreases with the increase of the cross-linking agent; it has a good self-lubricating effect, the friction coefficient is 0.06-0.12, and the friction coefficient is low; the underwater heavy oil contact angle is 135-150°; the drag reduction rate is 25-40%, and it has excellent drag reduction performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The SEM surface photograph of the low-friction acrylic coating with the characteristic of gradual and controllable hydrolysis of the interface provided in Application Example 3 of the present invention after degradation;

[0043] Figure 2 This is a SEM cross-sectional photograph of the low-friction acrylic coating with the characteristic of gradual and controllable hydrolysis of the interface provided in Application Example 3 of the present invention after degradation;

[0044] Figure 3 The friction coefficient curve of the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis provided in Application Example 3 of the present invention after degradation by weak alkaline solution under the conditions of load 1N and frequency 1Hz for 10h. DETAILED DESCRIPTION

[0045] The present invention provides an acrylic resin hydrolyzed under weak alkaline conditions, which is obtained by polymerizing the following raw materials in parts by weight:

[0046] 10 to 15 parts of a degradable polymerizable silicone monomer, 30 to 60 parts of a non-degradable acrylic acid monomer and a non-degradable acrylate monomer, 1 to 1.5 parts of an initiator, and 50 to 75 parts of an organic solvent (hereinafter referred to as the first organic solvent);

[0047] The non-degradable acrylic acid ester monomer comprises a first acrylic acid ester monomer, a second acrylic acid ester monomer and β-hydroxyethyl methacrylate, wherein the first acrylic acid ester monomer comprises methyl methacrylate and / or ethyl acrylate, and the second acrylic acid ester monomer comprises butyl acrylate and / or methoxyethyl methacrylate;

[0048] The degradable polymerizable silicone monomer is an acrylic silicone ester monomer, and its structural formula is shown in Formula I:

[0049]

[0050] In formula I, R1 is H or methyl.

[0051] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0052] The present invention provides an acrylic resin hydrolyzed under weak alkaline conditions, wherein the pH value of the weak alkaline conditions is preferably 8-9.

[0053] In terms of mass fraction, the raw material for preparing the acrylic resin hydrolyzed under weak alkaline conditions provided by the present invention includes 10 to 15 parts of a degradable polymerizable silicone monomer, preferably 11 to 14 parts, more preferably 12 to 13 parts, and specifically 14 parts in the embodiment. In the present invention, the degradable polymerizable silicone monomer is an acrylic silicone ester monomer, and the structural formula of the degradable polymerizable silicone monomer is shown in Formula I.

[0054] Based on the mass fraction of the degradable polymerizable silicone monomer, the raw material for preparing the acrylic resin hydrolyzed under weak alkaline conditions provided by the present invention includes 30 to 60 parts of the sum of non-degradable acrylic monomers and non-degradable acrylic ester monomers, preferably 35 to 45 parts, and more preferably 38 to 42 parts. In the present invention, the non-degradable acrylic monomer can be acrylic acid. The non-degradable acrylic ester monomer includes a first acrylic ester monomer, a second acrylic ester monomer and β-hydroxyethyl methacrylate, the first acrylic ester monomer includes methyl methacrylate and / or ethyl acrylate, and the second acrylic ester monomer includes butyl acrylate and / or methoxyethyl methacrylate. In the present invention, the non-degradable acrylic ester monomer preferably includes methyl methacrylate, butyl acrylate and β-hydroxyethyl methacrylate. The mass ratio of methyl methacrylate, butyl acrylate, β-hydroxyethyl methacrylate and non-degradable acrylic acid monomer is preferably (4-8):(6-10):(8-12):(12-16), more preferably (5-8):(8-10):(10-12):(12-16), further preferably (4.5-5.5):(7-9):(9-11):(13-15) or (6-7):(8.5-9.5):(10.5-11.5):(14-15).

[0055] In an embodiment of the present invention, the non-degradable acrylic ester monomers are specifically methyl methacrylate, butyl acrylate and β-hydroxyethyl methacrylate. Based on the mass fraction of the degradable polymerizable silicone monomers, the raw materials of the acrylic resin hydrolyzed under weak alkaline conditions provided by the present invention include 6 parts of methyl methacrylate, 8 parts of butyl acrylate, 10 parts of β-hydroxyethyl methacrylate and 14 parts of acrylic acid.

[0056] Based on the mass fraction of the degradable polymerizable silicone monomer, the raw material for preparing the acrylic resin hydrolyzed under weak alkaline conditions provided by the present invention includes 1 to 1.5 parts of initiator, preferably 1.1 to 1.4 parts, more preferably 1.2 to 1.3 parts, and specifically 1.5 parts in the embodiment. In the present invention, the initiator is preferably azobisisobutyronitrile.

[0057] Based on the mass fraction of the degradable polymerizable silicone monomer, the raw material for preparing the acrylic resin hydrolyzed under weak alkaline conditions provided by the present invention includes 50 to 75 parts of a first organic solvent, preferably 52 to 68 parts, more preferably 55 to 65 parts, and specifically 75 parts in the embodiment. In the present invention, the first organic solvent is preferably xylene and N,N-dimethylformamide. The mass ratio of xylene to N,N-dimethylformamide is preferably (1 to 2):(1 to 2), and more preferably (1 to 1.5):(1 to 1.5). The present invention does not specifically limit the preparation method of the first organic solvent, and the components of the organic solvent can be directly mixed.

[0058] In the present invention, the acrylic resin hydrolyzed under weak alkaline conditions is obtained by polymerizing a degradable polymerizable silicone monomer, non-degradable acrylic acid and a non-degradable acrylic ester compound; the acrylic resin hydrolyzed under weak alkaline conditions has a structure as shown in Formula II:

[0059]

[0060] In formula II, R1 is -H or methyl.

[0061] The present invention provides a method for preparing an acrylic resin hydrolyzed under weakly alkaline conditions as described in the above technical scheme, comprising the following steps:

[0062] A degradable polymerizable silicone monomer, a non-degradable acrylic monomer, a non-degradable acrylate monomer, an initiator and a first organic solvent are mixed to obtain a mixed solution; the mixed solution is subjected to a polymerization reaction to obtain an acrylic resin hydrolyzed under the weak alkaline condition.

[0063] In the present invention, the mixing sequence preferably includes: dissolving the initiator in the first organic solvent to obtain an initiator solution; stirring and mixing the initiator solution, the degradable polymerizable silicone monomer, the non-degradable acrylic monomer and the non-degradable acrylic ester monomer to obtain a mixed solution. The dissolution is preferably carried out under stirring.

[0064] In the present invention, the polymerization reaction temperature is preferably 85-95°C, more preferably 87-93°C, and further preferably 88-92°C. In a specific embodiment of the present invention, the polymerization reaction is carried out in a three-necked flask. In the present invention, the polymerization reaction preferably includes the following steps:

[0065] Part of the mixed solution is subjected to a first stage polymerization reaction to obtain a prepolymerization reaction solution. In the present invention, the percentage of the part of the mixed solution to the total mass of the mixed solution is preferably 25-35wt.%, specifically 30wt.%. The reaction time of the first stage polymerization reaction is preferably 25-40min, more preferably 25-35min, and further preferably 28-32min.

[0066] After obtaining the prepolymerization reaction liquid, the present invention drips the remaining mixed solution into the prepolymerization reaction liquid to carry out a second-stage polymerization reaction to obtain an acrylic resin hydrolyzed under the weakly alkaline condition. In the present invention, the remaining mixed solution accounts for a percentage of 65 to 75 wt.%, specifically 70 wt.% of the total mass of the mixed solution. The dripping speed is preferably 0.8 to 1.2 mL / min, and more preferably 0.9 to 1.1 mL / min. In the present invention, the dripping is preferably carried out under stirring, and the stirring is preferably mechanical stirring, and the stirring rate is preferably 200 to 400 rpm, and more preferably 220 to 380 rpm. After the dripping is completed, the insulation reaction time of the second-stage polymerization reaction is preferably 2 to 3 hours, more preferably 2.3 to 2.8 hours, and more preferably 2.4 to 2.8 hours.

[0067] In the present invention, the solid content of the acrylic acid hydrolyzed under weak alkaline conditions is preferably 35-45%, more preferably 38-42%, and even more preferably 39-41%.

[0068] The present invention provides the use of the acrylic resin hydrolyzed under weak alkaline conditions described in the above technical solution or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in the above technical solution in a low-friction acrylic coating with degradable characteristics.

[0069] In the present invention, the acrylic resin hydrolyzed under weak alkaline conditions is used as a raw material for preparing the low-friction acrylic coating with degradable characteristics.

[0070] The present invention provides a low-friction acrylic paint with degradable properties, comprising the following components in parts by weight:

[0071] 40-60 parts of acrylic resin hydrolyzed under weak alkaline conditions;

[0072] 10-15 parts of wear-resistant filler;

[0073] 10-15 parts of pigments and fillers;

[0074] 1-2 parts of auxiliary agent;

[0075] 15 to 25 parts of an organic solvent (hereinafter referred to as the second organic solvent);

[0076] The acrylic resin hydrolyzed under weak alkaline conditions is the acrylic resin hydrolyzed under weak alkaline conditions described in the above technical solution or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in the above technical solution.

[0077] In terms of weight, the low-friction acrylic coating with biodegradable properties provided by the present invention comprises 40 to 60 parts of acrylic resin hydrolyzed under weak alkaline conditions, preferably 42 to 55 parts, more preferably 45 to 50 parts, and specifically 60 parts, 50 parts, and 40 parts in the embodiments. In the present invention, the acrylic resin hydrolyzed under weak alkaline conditions is the acrylic resin hydrolyzed under weak alkaline conditions described in the above technical solution or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in the above technical solution.

[0078] Based on the mass fraction of the acrylic resin hydrolyzed under the weak alkaline conditions, the low-friction acrylic coating with degradable characteristics provided by the present invention includes 10 to 15 parts of wear-resistant fillers, preferably 11 to 14 parts, and more preferably 12 to 13 parts. In the present invention, the wear-resistant filler preferably includes precipitated barium sulfate, mica powder and brown corundum; the mass ratio of the precipitated barium sulfate, mica powder and brown corundum is preferably (1 to 1.8): (1 to 1.8): (1 to 2), more preferably (1 to 1.5): (1 to 1.5): (1 to 2), and further preferably (1.2 to 1.5): (1.2 to 1.5): (1.2 to 1.8). The most preferred is (1.2 to 1.4): (1.2 to 1.4): (1.2 to 1.8). In the present invention, the wear-resistant filler is conducive to improving the mechanical properties of the coating formed by the low-friction acrylic coating and improving the wear resistance.

[0079] In an embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the low-friction acrylic coating with biodegradable properties provided by the present invention includes 3 parts of precipitated barium sulfate, 3 parts of mica powder, and 4 parts of brown corundum.

[0080] Based on the mass fraction of the acrylic resin hydrolyzed under the weak alkaline condition, the low-friction acrylic coating with degradable characteristics provided by the present invention includes 10 to 15 parts of pigments and fillers, preferably 11 to 14 parts, and more preferably 12 to 13 parts. In the present invention, the pigments and fillers preferably include organic bentonite, kaolin, red iron oxide and zinc oxide; the mass ratio of the organic bentonite, kaolin, red iron oxide and zinc oxide is preferably (1 to 1.8): (1 to 1.8): (1 to 2): 1, more preferably (1 to 1.5): (1 to 1.5): (1 to 2): 1, further preferably (1.2 to 1.5): (1.2 to 1.5): (1.2 to 1.8): 1, and most preferably (1.2 to 1.4): (1.2 to 1.4): (1.2 to 1.8): 1. In the present invention, the pigments and fillers are conducive to enhancing the mechanical properties of the coating formed by the low-friction acrylic coating with degradable characteristics, improving the thixotropic properties of the coating, and reducing the cost of the coating.

[0081] In a specific embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the low-friction acrylic coating with biodegradable properties provided by the present invention includes 2.5 parts of organic bentonite, 2.5 parts of kaolin, 4 parts of red iron oxide and 2 parts of zinc oxide.

[0082] In a specific embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the low-friction acrylic coating with biodegradable properties provided by the present invention includes 4 parts of red iron oxide, 2 parts of zinc oxide, 2.5 parts of organic bentonite and 2.5 parts of kaolin.

[0083] Based on the mass fraction of the acrylic resin hydrolyzed under the weak alkaline conditions, the low-friction acrylic coating with degradable characteristics provided by the present invention includes 1 to 2 parts of additives, preferably 1.2 to 1.8 parts, and more preferably 1.3 to 1.7 parts. In the present invention, the additives preferably include a wetting dispersant, a leveling agent, a defoamer, and an anti-settling agent. The wetting dispersant is specifically BYK163 and BYK104s, and the mass ratio of BYK163 to BYK104s is preferably 1:1. The leveling agent is preferably BYK300, BYK333 or BYK354, specifically BYK354, the defoamer is preferably BYK052 or Tiger 386N, specifically BYK052, and the anti-settling agent is specifically BYK410. The mass ratio of the wetting and dispersing agent, leveling agent, defoaming agent and anti-settling agent is preferably (1-3): (1-2): (1-2): (1-2), and more preferably (1-2.5): (1-1.8): (1-1.8): (1-1.8) or (1.3-2.7): (1-1.5): (1-1.5): (1.2-1.8). In the present invention, the auxiliary agent is beneficial to reducing the apparent defects of the coating formed by the low-friction self-lubricating coating, and improving the surface gloss, smoothness and flatness of the coating; at the same time, it improves the uniform dispersion of the filler in the coating system, which is beneficial to improving the construction performance of the coating, enhancing the wettability of the coating formed by the low-friction self-lubricating coating with the substrate, and improving the bonding force.

[0084] In a specific embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the additives in the low-friction acrylic coating with biodegradable properties provided by the present invention include 0.3 parts of wetting and dispersing agent BYK163, 0.3 parts of wetting and dispersing agent BYK104s, 0.3 parts of anti-settling agent BYK410, 0.25 parts of defoaming agent BYK052 and 0.35 parts of leveling agent BYK354.

[0085] In a specific embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the additives in the low-friction acrylic coating with biodegradable properties provided by the present invention include 0.258 parts of wetting and dispersing agent BYK163, 0.258 parts of wetting and dispersing agent BYK104s, 0.258 parts of anti-settling agent BYK410, 0.215 parts of defoaming agent BYK052 and 0.3 parts of leveling agent BYK354.

[0086] In a specific embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the additives in the low-friction acrylic coating with biodegradable properties provided by the present invention include 0.228 parts of wetting and dispersing agent BYK163, 0.228 parts of wetting and dispersing agent BYK104s, 0.228 parts of anti-settling agent BYK410, 0.19 parts of defoaming agent BYK052 and 0.266 parts of leveling agent BYK354.

[0087] Based on the mass fraction of the acrylic resin hydrolyzed under the weak alkaline conditions, the low-friction acrylic coating with degradable properties provided by the present invention includes 15 to 25 parts of a second organic solvent, preferably 17 to 23 parts, and more preferably 19 to 22 parts. In the present invention, the second organic solvent is preferably xylene, N,N-dimethylformamide and n-butanol, and the mass ratio of xylene, N,N-dimethylformamide and n-butanol is preferably (1 to 2):(1 to 2):(1 to 2), and further preferably (1.2 to 1.8):(1.2 to 1.8):(1.2 to 1.8). In the present invention, the organic solvent is beneficial to improving the viscosity of the low-friction acrylic coating and improving the film-forming properties of the coating; it is also beneficial to the construction of the coating.

[0088] In a specific embodiment of the present invention, based on the mass fraction of the acrylic resin hydrolyzed under the weakly alkaline conditions, the second organic solvent in the low-friction acrylic coating with degradable properties provided by the present invention includes 5 parts of xylene, 5 parts of N,N-dimethylformamide and 5 parts of n-butanol.

[0089] In the present invention, the method for preparing the low-friction acrylic coating having degradable properties preferably comprises the following steps:

[0090] The acrylic resin hydrolyzed under weak alkaline conditions, the additive and the second organic solvent are mixed to obtain a primary mixture;

[0091] The primary mixed material, the wear-resistant filler and the pigment filler are mixed to obtain the low-friction acrylic paint with degradable characteristics.

[0092] In the present invention, the mixing of the acrylic resin hydrolyzed under weak alkaline conditions, the auxiliary agent and the organic solvent is preferably carried out under stirring conditions; the stirring rate is preferably 300-400 rpm, more preferably 320-380 rpm; the time is preferably 25-35 min, more preferably 27-32 min, and most preferably 30 min.

[0093] In the present invention, the mixing of the primary mixture, the wear-resistant filler and the pigment filler is preferably carried out by stirring and ball milling in sequence. In the present invention, the stirring rate is preferably 500-700rpm, more preferably 550-600rpm; the time is preferably 25-35min, more preferably 27-32min, and most preferably 30min. In the present invention, the rotation speed of the ball mill is preferably 1500-2000rpm, more preferably 1600-1900rpm; the time is preferably 4-8h, more preferably 5-6h. In the present invention, the ball-to-material ratio in the ball mill is preferably (1-4):2, more preferably (1.5-3):2. In the present invention, the equipment for the ball milling is preferably a ball mill, more preferably a planetary ball mill. In an embodiment of the present invention, the model of the planetary ball mill is preferably QM-3SP2. In the present invention, the fineness of the low-friction acrylic paint with degradable properties is preferably ≤40μm.

[0094] After the ball milling, the present invention preferably filters the obtained ball milled material to remove impurities or large particle agglomerates to ensure the fineness of the low-friction acrylic paint with degradable characteristics.

[0095] The present invention provides the use of the low-friction acrylic paint with degradable characteristics described in the above technical solution in a low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of the interface.

[0096] In the present invention, the application is specifically: using a low-friction acrylic paint with degradable properties to prepare the low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of the interface on the surface of the substrate.

[0097] The invention provides a low-friction acrylic coating with the characteristic of gradual and controllable hydrolysis of the interface, comprising the following raw materials in parts by weight: 10 to 20 parts of the low-friction acrylic coating with degradable characteristics described in the above technical solution and 0.1 to 0.3 parts of a crosslinking agent.

[0098] In terms of weight, the raw materials for preparing the low-friction acrylic coating with the characteristic of gradual and controllable interface hydrolysis provided by the present invention include 10 to 20 parts, preferably 10 to 15 parts, specifically 10 parts, of the low-friction acrylic coating with degradable properties described in the above technical solution.

[0099] Based on the mass fraction of the low-friction acrylic coating with degradable properties, the raw materials for preparing the low-friction acrylic coating with the characteristics of gradual controllable hydrolysis of the interface provided by the present invention include 0.1 to 0.3 parts of a crosslinking agent, preferably 0.15 to 0.25 parts, more preferably 0.15 to 0.2 parts, specifically 0.195 parts, 0.181 parts, 0.164 parts, 0.137 parts, 0.109 parts, and 0.191 parts. In the present invention, the crosslinking agent is preferably an isocyanate crosslinking agent. In the present invention, the crosslinking agent is more preferably toluene-2,4-diisocyanate and / or diphenylmethane diisocyanate.

[0100] In the present invention, the amount of the cross-linking agent is preferably such that the molar ratio of the isocyanate cross-linking agent to the raw material of the acrylic resin hydrolyzed under weak alkaline conditions in the low-friction acrylic coating with degradable properties, β-hydroxyethyl methacrylate, satisfies (0.5-1.5):1, further satisfies (0.7-1.3):1, and most preferably satisfies (0.714-1.25):1. On the basis of meeting the above requirements, the low-friction acrylic coating with gradually controllable interface hydrolysis provided by the present invention comprises 10-20 parts of the low-friction acrylic coating with degradable properties as described in the above technical scheme and 0.1-0.3 parts of the cross-linking agent.

[0101] In the present invention, the crosslinking agent is conducive to the formation of a crosslinked network structure of the coating, which is conducive to improving the stability and mechanical properties of the coating. At the same time, the present invention controls the hydrolysis rate of the coating by controlling the amount of the crosslinking agent, giving the coating a controllable degradation property. In the present invention, the amount of the crosslinking agent depends on the degree of crosslinking; the degree of crosslinking is preferably 50% to 70%, more preferably 55% to 65%, and most preferably 60%. In the 60% crosslinking degree, the molar ratio of β-hydroxyethyl methacrylate to toluene-2,4-diisocyanate is preferably 1.2:1.

[0102] The present invention provides a method for preparing a low-friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface as described in the above technical solution, comprising the following steps:

[0103] The low-friction acrylic coating with degradable properties described in the above technical solution, a crosslinking agent and an organic solvent (hereinafter referred to as the third organic solvent) are mixed and coated on the surface of the substrate to obtain an initial wet film;

[0104] The initial wet grinding is dried to obtain a low-friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface on the surface of the substrate.

[0105] The present invention mixes the low-friction acrylic paint with degradable properties, a crosslinking agent and an organic solvent (hereinafter referred to as the third organic solvent) described in the above technical solution and then applies them on the surface of the substrate to obtain an initial wet film. In the present invention, the mass ratio of the low-friction acrylic paint with degradable properties and the third organic solvent is preferably (10-20): (4-8), more preferably 10-15: (4-8), specifically 10:5. The present invention preferably reduces the viscosity of the mixture formed by the low-friction acrylic paint with degradable properties and the crosslinking agent through the third organic solvent, thereby improving the film-forming performance of the diluted paint formed by the mixture of the low-friction acrylic paint with degradable properties, the crosslinking agent and the third organic solvent on the surface of the substrate.

[0106] In the present invention, the third organic solvent is preferably xylene, N,N-dimethylformamide and n-butanol; the mass ratio of xylene, N,N-dimethylformamide and n-butanol is preferably (1-2):(1-2):(1-2), and further preferably (1-1.5):(1-1.5):(1-1.5).

[0107] In the present invention, the substrate is preferably an epoxy substrate. Before the coating, the substrate is preferably cleaned to obtain a clean substrate. In the present invention, the coating method is preferably spraying or brushing.

[0108] After obtaining the initial wet film, the present invention dries the initial wet grinding to obtain a low-friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface on the surface of the substrate. In the present invention, the drying can be carried out at room temperature, and the drying time can be 24 to 48 hours. The present invention has no special limitation on the drying, and the drying method well known to those skilled in the art can be used. The present invention forms a solid film after drying, in which most of the third organic solvent will volatilize, and there may be a small amount of residue.

[0109] In the present invention, the thickness of the low-friction acrylic coating with the characteristic of gradual controllable hydrolysis of the interface is preferably 100-200 μm, more preferably 120-180 μm. In the present invention, the coating amount is based on the thickness of the low-friction acrylic coating with the characteristic of gradual controllable hydrolysis of the interface.

[0110] The low-friction acrylic coating with the characteristic of gradually controllable hydrolysis of the interface obtained by the invention is firmly combined with the substrate.

[0111] The present invention provides the use of the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis as described in the above technical solution or the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis prepared by the preparation method described in the above technical solution as a lubricating material in an alkaline environment.

[0112] In the present invention, the application preferably includes: applying the low-friction acrylic coating having the characteristic of gradually controllable hydrolysis of the interface to marine engineering lubricating materials.

[0113] The low-friction acrylic coating with the characteristic of gradually controlled hydrolysis of the interface provided by the present invention (taking the coating prepared in Application Example 3 as an example) is continuously immersed in a weak alkaline solution, and the surface SEM photograph after freeze-drying is shown in FIG. Figure 1 , cross-sectional SEM photos are shown in Figure 2 ; Under the conditions of load 1N and frequency 1Hz, the friction coefficient curve of 10h long rubbing is shown in Figure 3 . In the present invention, the acrylic resin hydrolyzed under weak alkaline conditions ensures that the interface is gradually degraded to form a water lubrication layer, the chemical cross-linking structure ensures the controllable degradation of the coating, and the wear-resistant filler ensures that the coating has good wear resistance. The acrylic coating prepared by this feature is jointly determined by the acrylic silicon content and chemical cross-linking to form a degradation hydration layer at the micron scale under weak alkaline conditions. Combined with the wear-resistant filler, it has a low interface friction coefficient and stable wear resistance. This feature takes into account the characteristics of top surface friction reduction and bottom surface wear resistance. And the micron-scale hydration layer can be continuously renewed as the interface wears, and has typical low-friction self-renewal characteristics.

[0114] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0115] The parts in the following examples are parts by mass.

[0116] Example 1

[0117] Preparation of acrylic resin hydrolyzed under weak alkaline conditions: first, weigh 1.5 parts of azobisisobutyronitrile, 37.5 parts of xylene and N,N-dimethylformamide in a beaker, and then stir thoroughly to completely dissolve the azobisisobutyronitrile; then continue to weigh 6 parts of methyl methacrylate, 8 parts of butyl acrylate, 10 parts of β-hydroxyethyl methacrylate, 12 parts of triisopropylsilyl acrylate, and 14 parts of acrylic acid in a beaker and stir thoroughly to mix uniformly to obtain a mixture solution; then weigh 30% of the mixture solution by weight in a flask, react at 90° C. under mechanical stirring for 30 minutes, and then add the remaining 70% of the mixture solution to the flask at a drop rate of 1.0 mL / min. After the dropwise addition is completed, continue to keep warm for 2 hours for polymerization reaction to obtain an acrylic resin hydrolyzed under weak alkaline conditions with a solid content of 40%.

[0118] Example 2

[0119] In parts by mass, 60 parts of the acrylic resin hydrolyzed under weak alkaline conditions obtained in Example 1, 0.3 parts of wetting and dispersing agent BYK163, 0.3 parts of wetting and dispersing agent BYK104s, 0.3 parts of anti-settling agent BYK410, 0.25 parts of defoaming agent BYK052, 0.35 parts of leveling agent BYK354, 5 parts of xylene, 5 parts of N,N-dimethylformamide, and 5 parts of n-butanol were mixed uniformly to obtain a primary mixture; the obtained primary mixture and 3 parts of Precipitated barium sulfate, 3 parts of mica powder, 4 parts of brown corundum, 4 parts of red iron oxide, 2 parts of zinc oxide, 2.5 parts of organic bentonite and 2.5 parts of kaolin were mixed, stirred and dispersed at a speed of 300 rpm for 30 minutes, and then ball-milled at a speed of 3000 rpm for 6 hours in a QM-3SP2 planetary ball mill. After the material was discharged, it was filtered to obtain a low-friction acrylic coating with a solid content of 46.9wt% and a fineness of less than 40μm and having biodegradable properties.

[0120] Example 3

[0121] In parts by mass, 50 parts of the acrylic resin hydrolyzed under weak alkaline conditions obtained in Example 1, 0.258 parts of wetting and dispersing agent BYK163, 0.258 parts of wetting and dispersing agent BYK104s, 0.258 parts of anti-settling agent BYK410, 0.215 parts of defoaming agent BYK052, 0.3 parts of leveling agent BYK354, 5 parts of xylene, 5 parts of N,N-dimethylformamide, and 5 parts of n-butanol were mixed uniformly to obtain a primary mixture; the obtained primary mixture was , 3 parts of precipitated barium sulfate, 3 parts of mica powder, 4 parts of brown corundum, 4 parts of red iron oxide, 2 parts of zinc oxide, 2.5 parts of organic bentonite and 2.5 parts of kaolin were mixed, stirred and dispersed at 300 rpm for 30 minutes, and then ball-milled at 3000 rpm for 6 hours in a QM-3SP2 planetary ball mill. After discharging, the material was filtered to obtain a low-friction acrylic coating with a solid content of 47.7wt% and a fineness of less than 40μm and biodegradable properties.

[0122] Example 4

[0123] In parts by mass, 40 parts of the acrylic resin hydrolyzed under weak alkaline conditions obtained in Example 1, 0.228 parts of wetting and dispersing agent BYK163, 0.228 parts of wetting and dispersing agent BYK104s, 0.228 parts of anti-settling agent BYK410, 0.19 parts of defoaming agent BYK052, 0.266 parts of leveling agent BYK354, 5 parts of xylene, 5 parts of N,N-dimethylformamide, and 5 parts of n-butanol were mixed uniformly to obtain a primary mixture; the obtained primary mixture was The raw material, 3 parts of precipitated barium sulfate, 3 parts of mica powder, 4 parts of brown corundum, 4 parts of red iron oxide, 2 parts of zinc oxide, 2.5 parts of organic bentonite and 2.5 parts of kaolin were mixed, stirred and dispersed at a speed of 300 rpm for 30 minutes, and then ball-milled at a speed of 3000 rpm for 6 hours in a QM-3SP2 planetary ball mill. After the material was discharged, it was filtered to obtain a low-friction acrylic coating with a solid content of 48.7wt% and a fineness of less than 40μm and having biodegradable properties.

[0124] Application Example 1

[0125] Weigh 10 parts of the low-friction acrylic coating with biodegradable properties obtained in Example 2, weigh 0.195 parts of toluene-2,4-diisocyanate, and 5 parts of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1 to dilute the coating. After sufficient stirring, spray the diluted coating on the epoxy substrate and dry it at room temperature for 24 hours to obtain a low-friction acrylic coating with a solid content of 46.9wt%, a crosslinking degree of 60%, and a thickness of about 150μm and the characteristics of gradually controllable interface hydrolysis.

[0126] Application Example 2

[0127] Weigh 10 parts of the low-friction acrylic coating with biodegradable properties obtained in Example 3, weigh 0.181 g of toluene-2,4-diisocyanate, and 5 parts of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1 to dilute the coating, stir thoroughly, spray the diluted coating on the epoxy substrate, and dry at room temperature for 24 hours to obtain a low-friction acrylic coating with a solid content of 47.7 wt%, a cross-linking degree of 60%, and a thickness of about 150 μm and the characteristics of gradually controllable interface hydrolysis.

[0128] Application Example 3

[0129] Weigh 10 parts of the low-friction acrylic coating with biodegradable properties obtained in Example 4, weigh 0.164 parts of toluene-2,4-diisocyanate, and 5 parts of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1 to dilute the coating. After sufficient stirring, spray the diluted coating on the epoxy substrate and dry it at room temperature for 24 hours to obtain a low-friction acrylic coating with a solid content of 48.7wt%, a crosslinking degree of 60%, and a thickness of about 150μm and the characteristics of gradually controllable interface hydrolysis.

[0130] Application Example 4

[0131] Weigh 10 parts of the low-friction acrylic coating with biodegradable properties obtained in Example 4, weigh 0.137 parts of toluene-2,4-diisocyanate, and 5 parts of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1 to dilute the coating, stir thoroughly, spray the diluted coating on the epoxy substrate, and dry at room temperature for 24 hours to obtain a low-friction acrylic coating with a solid content of 48.7wt%, a crosslinking degree of 50%, and a thickness of about 150μm and the characteristics of gradually controllable interface hydrolysis.

[0132] Application Example 5

[0133] Weigh 10 parts of the low-friction acrylic coating with biodegradable properties obtained in Example 4, weigh 0.109 parts of toluene-2,4-diisocyanate, and 5 parts of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1 to dilute the coating, stir thoroughly, spray the diluted coating on the epoxy substrate, and dry at room temperature for 24 hours to obtain a low-friction acrylic coating with a solid content of 48.7wt%, a crosslinking degree of 40%, and a thickness of about 150μm and the characteristics of gradually controllable interface hydrolysis.

[0134] Application Example 6

[0135] Weigh 10 parts of the low-friction acrylic coating with biodegradable properties obtained in Example 4, weigh 0.191 parts of toluene-2,4-diisocyanate, and 5 parts of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1 to dilute the coating, stir thoroughly, spray the diluted coating on the epoxy substrate, and dry at room temperature for 24 hours to obtain a low-friction acrylic coating with a solid content of 48.7wt%, a crosslinking degree of 70%, and a thickness of about 150μm and the characteristics of gradually controllable interface hydrolysis.

[0136] The following tests were performed on the low-friction acrylic coatings with the characteristics of gradual controllable hydrolysis of the interface obtained in Examples 1 to 6:

[0137] Adhesion test is carried out according to GB1720-79;

[0138] The underwater oil contact angle was measured by using a contact angle meter, in which dichloromethane was used as the heavy oil to test the underwater oil contact angle;

[0139] The drag reduction rate was measured using a rheometer;

[0140] The friction coefficient was tested by a ball-on-disc friction tester, in which the PDMS balls were used as pairs, the weak alkaline solution was used as the lubricating medium, the frequency was 1 Hz, and the amplitude was 5 mm;

[0141] The coating was immersed in a weak alkaline solution of about pH 8±0.5 for a hydrolysis test. The specific test method is as follows: the coating prepared in Application Examples 1 to 6 was immersed in a weak alkaline solution of about pH 8±0.5 (sodium hydroxide aqueous solution or artificial seawater) for a hydrolysis reaction, and the friction coefficient of the coating was tested after taking it out at different time intervals until the friction coefficient of the hydrolyzed coating no longer decreased, and the minimum friction coefficient after hydrolysis and the time taken for hydrolysis to reach the minimum friction coefficient were recorded.

[0142] The test results are shown in Table 1.

[0143] Table 1 Test results of low friction acrylic coatings with interface stepwise controlled hydrolysis characteristics in application examples 1 to 6

[0144]

[0145] As can be seen from Table 1, the low-friction acrylic coating with degradable properties provided by Application Examples 1 to 6 of the present invention has a first-grade adhesion to the substrate and a high bonding force; when the coating prepared by Application Examples 1 to 6 is used in an alkaline environment, the coating will hydrolyze, and the friction coefficient of the coating will decrease accordingly. The minimum friction coefficient of the coating after hydrolysis is 0.06 to 0.12; the underwater dichloromethane contact angle is 140 to 149°, the drag reduction rate is 26 to 35%, and it has good self-lubricating properties. In addition, it can be seen from Application Examples 3 to 6 that the hydrolysis rate of the coating can be controlled by controlling the crosslinking degree of the coating.

[0146] The friction coefficients of the coatings obtained by drying at room temperature for 24 hours in Application Examples 1 to 6 (not immersed in a weakly alkaline solution) are: 0.32 for the coating in Application Example 1, 0.25 for the coating in Application Example 2, 0.24 for the coating in Application Example 3, 0.20 for the coating in Application Example 4, 0.22 for the coating in Application Example 5, and 0.28 for the coating in Application Example 6.

[0147] By comparing the initial friction coefficients of Application Examples 1 to 6 before immersion in a weak alkaline solution and the friction coefficients after stabilization in the weak alkaline solution in Table 1, it can be seen that the self-lubricating acrylic resin coatings with degradable properties provided by Application Examples 1 to 6 of the present invention have a lower friction coefficient after being immersed in a weak alkaline solution, indicating that when the self-lubricating acrylic resin coatings with degradable properties in the present invention are in service in a weak alkaline environment, as the service time increases, their lubricity is further improved after hydrolysis, which means that after the coating is degraded, its lubricity is further improved.

[0148] Comparative Example 1

[0149] Preparation of non-hydrolyzable acrylic resin: First, 1.14 parts of azobisisobutyronitrile, 28.5 parts of xylene and N,N-dimethylformamide are weighed in a beaker, and then fully stirred to completely dissolve the azobisisobutyronitrile; then 6 parts of methyl methacrylate, 8 parts of butyl acrylate, 10 parts of β-hydroxyethyl methacrylate, and 14 parts of acrylic acid are weighed in a beaker and fully stirred to mix uniformly to obtain a mixture solution; then 30% of the mixture solution by weight is weighed in a flask, and reacted at 90° C. under mechanical stirring for 30 minutes, and the remaining 70% of the mixture solution is added to the flask at a drop rate of 1.0 mL / min. After the dropwise addition is completed, the mixture is kept warm for 2 hours for polymerization reaction to obtain a non-hydrolyzable acrylic resin with a solid content of 40%.

[0150] In parts by mass, 40 parts of the acrylic resin prepared in this comparative example, 0.228 parts of wetting and dispersing agent BYK163, 0.228 parts of wetting and dispersing agent BYK104s, 0.228 parts of anti-settling agent BYK410, 0.19 parts of defoaming agent BYK052, 0.266 parts of leveling agent BYK354, 5 parts of xylene, 5 parts of N,N-dimethylformamide, and 5 parts of n-butanol were mixed uniformly to obtain a primary mixture; the obtained primary mixture was The raw material, 3 parts of precipitated barium sulfate, 3 parts of mica powder, 4 parts of brown corundum, 4 parts of red iron oxide, 2 parts of zinc oxide, 2.5 parts of organic bentonite and 2.5 parts of kaolin were mixed, stirred and dispersed at a speed of 300 rpm for 30 minutes, and then ball-milled at a speed of 3000 rpm for 6 hours in a QM-3SP2 planetary ball mill. After the material was discharged, it was filtered to obtain an acrylic resin coating with a solid content of 48.7wt% and a fineness of less than 40μm.

[0151] Weigh 10 parts of the acrylic resin coating prepared in this comparative example, weigh 0.216 parts of toluene-2,4-diisocyanate, and dilute the coating with an appropriate amount of a mixed solution of xylene, N,N-dimethylformamide, and n-butanol in a mass ratio of 1:1:1, stir thoroughly, and spray the diluted coating on the epoxy substrate. Dry at room temperature for 24 hours.

[0152] The friction coefficient of the coating obtained in Comparative Example 1 was tested according to the test method of Application Example 3, and the friction coefficient was measured to be 0.8.

[0153] By comparing the friction coefficients of Application Examples 1 to 3 and Comparative Example 1, it can be seen that the self-lubricating acrylic resin coating with biodegradable properties provided by the present invention has a lower friction coefficient, indicating that the polymerizable silicone monomer in the present invention can significantly improve the lubricity of the self-lubricating acrylic resin, thereby helping to reduce the friction of the coating.

[0154] It can be seen from the above embodiments that the low-friction acrylic coating with the characteristic of gradual controllable hydrolysis provided by the present invention is composed of an acrylic resin that can be hydrolyzed under weak alkaline conditions, a chemical crosslinking agent and a wear-resistant filler. In the present invention, the acrylic resin hydrolyzed under weak alkaline conditions ensures that the interface is gradually degraded to form a water lubrication layer, the chemical crosslinking structure ensures the controllable degradation of the coating, and the wear-resistant filler ensures that the coating has good wear resistance. The acrylic coating prepared by this feature is jointly determined by the acrylic silicon content and chemical crosslinking to form a degradation hydration layer at the micron scale under weak alkaline conditions. Combined with the wear-resistant filler, it has a low interface friction coefficient and stable wear resistance. This feature takes into account the characteristics of top surface friction reduction and bottom surface wear resistance. And the micron-scale hydration layer can be continuously updated as the interface wears, and has a typical low-friction self-renewal characteristic. Finally, the low-friction acrylic coating with the characteristic of gradual controllable hydrolysis provided by the present invention has a certain fluid drag reduction efficiency.

[0155] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An acrylic resin hydrolyzed under weak alkaline conditions, characterized in that It is obtained by polymerizing the following raw materials in parts by weight: 10-15 parts of degradable polymerizable silicone monomer, 30-60 parts of the sum of non-degradable acrylic acid monomer and non-degradable acrylate monomer, 1-1.5 parts of initiator, 50-75 parts of organic solvent; The non-degradable acrylic acid ester monomer comprises a first acrylic acid ester monomer, a second acrylic acid ester monomer and β-hydroxyethyl methacrylate, wherein the first acrylic acid ester monomer comprises methyl methacrylate and / or ethyl acrylate, and the second acrylic acid ester monomer comprises butyl acrylate and / or methoxyethyl methacrylate; The structural formula of the degradable polymerizable silicone monomer is shown in Formula I: In formula I, R1 is -H or methyl.

2. The acrylic resin hydrolyzed under weak alkaline conditions according to claim 1, characterized in that The non-degradable acrylic acid ester monomers include methyl methacrylate, butyl acrylate and β-hydroxyethyl methacrylate; The mass ratio of methyl methacrylate, butyl acrylate, β-hydroxyethyl methacrylate and non-degradable acrylic acid monomer is (4-8):(6-10):(8-12):(12-16); The initiator is azobisisobutyronitrile.

3. The method for preparing an acrylic resin hydrolyzed under weak alkaline conditions according to claim 1 or 2, characterized in that: The following steps are involved: A degradable polymerizable silicone monomer, a non-degradable acrylic acid monomer, a non-degradable acrylate monomer, an initiator and an organic solvent are mixed to obtain a mixed solution; the mixed solution is subjected to a polymerization reaction to obtain an acrylic resin hydrolyzed under the weak alkaline condition.

4. Use of the acrylic resin hydrolyzed under weak alkaline conditions according to claim 1 or 2 or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method according to claim 3 in a low-friction acrylic coating with degradable properties.

5. A low friction acrylic coating having degradable properties, characterized in that: The composition includes the following components in parts by weight: 40-60 parts of acrylic resin hydrolyzed under weak alkaline conditions; 10-15 parts of wear-resistant filler; 10-15 parts of pigments and fillers; 1-2 parts of auxiliary agent; 15-25 parts of organic solvent; The acrylic resin hydrolyzed under weak alkaline conditions is the acrylic resin hydrolyzed under weak alkaline conditions described in claim 1 or 2 or the acrylic resin hydrolyzed under weak alkaline conditions prepared by the preparation method described in claim 3.

6. The low-friction acrylic paint with degradable properties according to claim 5, characterized in that: The wear-resistant filler comprises precipitated barium sulfate, mica powder and brown corundum; the mass ratio of the precipitated barium sulfate, mica powder and brown corundum is (1-1.8):(1-1.8):(1-2); The pigment filler comprises organic bentonite, kaolin, red iron oxide and zinc oxide; the mass ratio of the organic bentonite, kaolin, red iron oxide and zinc oxide is (1-1.8):(1-1.8):(1-2):1; The auxiliary agents include a wetting and dispersing agent, a leveling agent, a defoaming agent and an anti-settling agent; the mass ratio of the wetting and dispersing agent, the leveling agent, the defoaming agent and the anti-settling agent is (1-3):(1-2):(1-2):(1-2).

7. Use of the degradable low-friction acrylic paint according to claim 5 or 6 in a low-friction acrylic coating having the characteristic of gradual and controllable hydrolysis of the interface.

8. A low friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface, characterized in that: The preparation method comprises the following raw materials in parts by mass: 10 to 20 parts of the low-friction acrylic paint with degradable properties as claimed in claim 5 or 6 and 0.1 to 0.3 parts of a cross-linking agent.

9. The method for preparing the low-friction acrylic coating with the characteristic of gradual and controllable hydrolysis of the interface as claimed in claim 8, characterized in that: The following steps are involved: The low-friction acrylic coating with degradable properties as claimed in claim 5 or 6, a crosslinking agent and an organic solvent are mixed and coated on the surface of the substrate to obtain an initial wet film; The initial wet grinding is dried to obtain a low-friction acrylic coating having the characteristics of gradual and controllable hydrolysis of the interface on the surface of the substrate.

10. Use of the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis as claimed in claim 8 or the low-friction acrylic coating with the characteristic of gradually controlled interface hydrolysis prepared by the preparation method of claim 9 as a lubricating material in an alkaline environment.

Citation Information

Patent Citations

  • Ultra-low friction coefficient self-lubricating coating and preparation method thereof

    CN110564260A

  • Preparation of silicone oil-containing lubricating anti-corrosion composite coating with low friction coefficient

    CN112266717A

  • Fluoroalkyl modified acrylate-containing low-surface energy, drag reduction and fouling prevention coating and preparation method thereof

    CN105542608A

  • Reactive acrylic resin as well as preparation method and application thereof

    CN112094369A

  • Acrylic resin with fouling inhibition and fouling release functions, preparation method and application thereof, and marine antifouling and drag-reducing coating

    CN115449034A